The Lexicostatistic Study Of Culambacu Language With Tolaki Language - La Ino Mbangi; La Ode Sidu Marafad (CAKRAWALA LINGUISTA, 2018)
Language Culambacu spoken by ethnic Culambacu contained in North Konawe district. This language has several dialects such as Lamonae dialect in Wiwirano Subdistrict, Landawe dialect in Oheo Subdistrict of North Konawe Regency, and Torete dialect is on the east coast of Konawe Regency in Waworaha Village. Tolaki language is spoken by ethnic tolaki located in Konawe District. This language has two dialects of Konawe dialect and Mekongga dialect. Based on the results of the analysis using lexicostatistic method found kinship relationship between Culambacu language with Tolaki language quantitatively is 39% vocabulary that is related to error rate 230. Both languages are separated from proto language estimated 3070 ± 230 years ago.